Next to love : a novel - Feldman, Ellen, 1941- (New York : Spiegel & Grau, 2011)
Follows the stories of three young couples whose lives are irrevocably changed in the years following World War II, a period during which they struggle with difficult losses and witness profound transformations in American culture.
Lariat Reading List, TLA 2012
Keywords: Female friendship -- Fiction; Massachusetts -- Fiction; Love stories; Historical fiction